1964
DOI: 10.2466/pr0.1964.15.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Social Desirability Values for California Psychological Inventory Items

Abstract: Social desirability ratings for CPI items were obtained from 68 female and 59 male college students. Simple means and standard deviations of the ratings were compared with previously published scale values and dispersions in the case of 186 overlapping CPI-MMPI items. The results showed high comparability on scale values so that the simple means of the item ratings may be used similarly to previously published MMPI item values obtained by using scaling techniques Simple standard deviations of individual item r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Similarly, the relationship between desirability and the factors was evaluated by computing the correlations between the items' scale values and their classifications on each factor, assigning scores of 1 to items with positive loadings, 0 to items with no loadings, and -1 to items with negative loadings. It is worth noting that such scale values are very stable over extended periods of time (Mees, Gocka, & Holloway, 1964;Messick & Jackson, 1961) and across diverse groups of subjects (see the reviews by Edwards, 1957Edwards, , 1967Edwards, , 1970Wiggins, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between desirability and the factors was evaluated by computing the correlations between the items' scale values and their classifications on each factor, assigning scores of 1 to items with positive loadings, 0 to items with no loadings, and -1 to items with negative loadings. It is worth noting that such scale values are very stable over extended periods of time (Mees, Gocka, & Holloway, 1964;Messick & Jackson, 1961) and across diverse groups of subjects (see the reviews by Edwards, 1957Edwards, , 1967Edwards, , 1970Wiggins, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the California Psychological Inventory (CPI; Gough, 1960), Mees, Gocka, and Holloway (1964) asked 68 women and 59 men to rate the SDSVs of its 480 items. Two features of this study are noteworthy in the present context.…”
Section: Rater Sex and Sdsvmentioning
confidence: 99%
“…The effect of target sex on judgments of SDSV was hinted at by the Mees et al () study referred to at the end of the previous section, where those authors asked men and women to rate personality items in terms of desirability as “applied to yourself” (p. 148). The sex of the target in mind for someone doing those ratings, of course, would correspond to the rater's own sex.…”
Section: Rater Sex and Sdsvmentioning
confidence: 99%
“…Previous researchers (e.g., Mees, Gocka, & Holloway, 1964) have demonstrated that SDSVs are not appeciably influenced by the statistical methods used for establishing them. Therefore, in order to avoid the complex method of successive intervals (Messick & Jackson, 1961), descriptive statistics were computed.…”
Section: Resalts and Discassionmentioning
confidence: 98%